Public culture and the making of national memory: Robert Burns in contemporary Scotland - Dougal, Josephine Kathleen (Curtin University, 2015)
This thesis is concerned with the relationship between public culture, cultural memory and national identity. Its purpose is to develop a critical account of the ways in which contemporary culture acts as a site for cultural memory and participates in the construction and representation of cultural identity, specifically Scottish identity. The topic is addressed through a detailed investigation of twenty first century representations of the eighteenth century Scottish poet and song writer, Robert Burns.